2014
DOI: 10.7763/ijtef.2014.v5.357
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Word-of-Mouth Factors on Consumers’ Buying Decision-Making Processes in the Low Cost Carriers: A Conceptual Framework

Abstract: Abstract-The purpose of this study is to develop a conceptual framework on the potential effects of electronic word-of-mouth (eWOM) communication on consumers' buying decision-making process in the low cost airline industry. A thorough review of literature reveals three main streams of factors affecting consumers' buying decisionmaking process involvement in eWOM in the low cost airline industry. These issues are the information provided by eWOM such as reviews, the creditability of channels used, volume of eW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Second, the present study emphasizes the complementary role of trust and satisfaction in influencing consumer behaviour such as recommending service providers; these are two key factor that affect loyalty and long term relationship (Kim et al, 2009;Sahin et al, 2011). Third, unlike previous studies that have emphasized the role of satisfaction and trust in developing strong client recommendations of service providers (File & Prince, 1992;Jiang, Shang, & Liu, 2010;Brown et al, 2005;Lerrthaitrakul & Panjakajornsak, 2014), the present study, has validated that, in financial service context, quality information provision is also an important determinant of customer recommendation of service providers.…”
Section: Theoretical Contributionmentioning
confidence: 56%
See 2 more Smart Citations
“…Second, the present study emphasizes the complementary role of trust and satisfaction in influencing consumer behaviour such as recommending service providers; these are two key factor that affect loyalty and long term relationship (Kim et al, 2009;Sahin et al, 2011). Third, unlike previous studies that have emphasized the role of satisfaction and trust in developing strong client recommendations of service providers (File & Prince, 1992;Jiang, Shang, & Liu, 2010;Brown et al, 2005;Lerrthaitrakul & Panjakajornsak, 2014), the present study, has validated that, in financial service context, quality information provision is also an important determinant of customer recommendation of service providers.…”
Section: Theoretical Contributionmentioning
confidence: 56%
“…Such positive perception could be influenced by the extent to which loan service provider has been able to explain in detail, all the necessary terms and conditions of the loan and communicate to customers, through quality information provision, any changes that may occur to loan terms and condition as well as the whole loan service delivery process (Allsop et al, Brown et al, 2005;Cengiz, & Yayla, 2007). In fact, the provision of quality information to clients regarding loan services could serve as an important means of generating and enhancing WOMC among customers (Shih, Lai, & Cheng, 2013;Sweeney et al, 2012;Sweeney, Soutar, & Mazzarol, 2014) and affect potential customers' decision making process (Lerrthaitrakul & Panjakajornsak, 2014). Failure to deliver quality information about loans to customer could result in consumer perceived deception which can generate negative WOMC about loan service provider (Mbawuni & Nimako, in press).…”
Section: Quality Of Loan Information (Inf) and Customer Recommendatiomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high motivation in using social media has also affected purchase intention (34). Some research has also confirmed the effect of E-WOM on purchase intention as in (16,35,36).…”
Section: Results and Findingsmentioning
confidence: 89%
“…The decline could be attributed to passengers' past experience with TransJakarta. Lerrthaitrakul and Panjakajornsak (2014) stated that when a passenger is satisfied with their public transportation experience, they will use it again and/or share their positive experience with other people, and vice versa. This shared experience can, in turn, affect the potential use of TransJakarta.…”
Section: Introductionmentioning
confidence: 99%